The Real Income Shares of Labor, Human and Physical Capital from Micro- and Macro-Data - Peter E.J. Steffen (Hamburg University, Department Socioeconomics, 2013)
Micro data are used to separate the wage income of employed workers into components of basic labor and human capital. Further on the wage components of the self employed are determined taking into account their higher qualification and longer working hours. The fractions of these wage components are used to obtain the total income shares of basic labor, human and physical capital from yearly GDP calculations. This procedure provides a yearly information on the development of the factor shares for individual countries, a tool for understanding development and growth. German census data of the years 1976, 1985, 1995, and 2006 are selected in order to demonstrate the method. As result the factor shares for these years are obtained. The average shares are in agreement with the well known results of Mankiw, Romer and Weil [8] if only employed workers are considered. If self-employed labor is also taken into account, the share ratios of physical and human capital and labor change to sK : sH : sL = 0:21 : 0:25 : 0:54. This result differs considerably from the generally expected share ratios for developed countries of 1/3 : 1/3 : 1/3. Further on, the development in time is investigated. A considerable variation is observed in the last period: 1995 - 2006. It is contradictory to a constant behavior as expected from Kaldor's stylized facts. The source could be traced to considerable changes in the qualification structure of the German work force.
Keywords: D33; E25; J24; 330; human capital; Mikrozensus; annual factor income shares; factor share development